LEARNING AGILITY AND DIGITAL LITERACY AS PREDICTORS OF POTENTIAL SCHOOL LEADERS - Nurkolis Nurkolis; Widya Kusumaningsih; Ghufron Abdullah (Program Studi PGSD Universitas Flores, 2025)
The selection of potential leaders in schools in Indonesia is still problematic. The objective of this study to determine the effect of learning agility and digital literacy on the potential future school leaders. This article is based on a quantitative research approach with a comparative causal design, a sample of 380 people with a simple random sampling. The research held in Kendal Regency, 2024-2025 school year. The instrument was tested and the results were valid and reliable. The research data were tested for prerequisites which showed normal, homogeneous, and linear. The research hypothesis was tested with Pearson product-moment correlation, determination test, and linear regression. The study result shows that there is positive, significant, and strong influence of learning agility on the potential of future school leaders; there is a strong, positive, and considerable influence of digital literacy on the potential future school leaders; and there is also positive, significant and strong influence of learning agility and digital literacy together on the potential future school leaders. This research contributes to the development of educational leadership concept from the aspect of teacher leadership. It is concluded that the selection of prospective teacher leaders needs to consider learning agility and digital literacy.